Adsorption of potentially toxic elements in water by modified biochar: A review. Issue 4 (August 2020) - Zhang, Ailin; Li, Xin; Xing, Jia; Xu, Guoren
Highlights: Modifications of biochar can enhance the sorption of heavy metals. Iron-modified biochar increases sorption of As(V), Cr (VI). Metal/metal oxide-biochar nanocomposites combine the adsorption advantages of biochar and nanomaterial. Finding a balance between optimizing performance and production costs is future goal. Abstract: Biochar, as a adsorbent, can remove potentially toxic elements (PTE) in water by physical adsorption, as well as chemical interactions such as ion exchange, electrostatic attraction, surface and inner sphere complexation, precipitation, and redox. However, unsatisfactory adsorption effects and difficult recovery of adsorbents limit the application of biochar as PTE adsorbent in water. Therefore, several methods of modifying biochar have been used to improve the removal efficiency of PTE (mainly includes heavy metals and metalloids), such as physical activation with steam, chemical modification with acids, bases, metals, metal oxides, organic compounds and carbon base materials. This review explains how these methods above change the adsorption mechanism, and which method is more suitable for adsorbing a certain target pollutant than others. Physical activation contributes to an increase in specific surface area of biochar, while chemical treatments enhance the proportion of oxygen-containing functional groups and introduce new particles as adsorption sites. We focus on the removal of Pb(II), Cd(II), Cu(II), Cr(VI), Cr(VI), and As(V), evaluate the effectiveness of different modification methods in removing these heavy metals and metalloids in water. The research direction of modified biochar is prospected.